Colorimetric gas detection by the varying thickness of a thin film of ultrasmall PTSA-coated TiO2 nanoparticles on a Si substrate - Joost, Urmas; Šutka, Andris; Visnapuu, Meeri; Tamm, Aile; Lembinen, Meeri; Antsov, Mikk; Utt, Kathriin; Smits, Krisjanis; Nõmmiste, Ergo; Kisand, Vambola (Beilstein Journal of Nanotechnology, 2017)
Colorimetric gas sensing is demonstrated by thin films based on ultrasmall TiO2 nanoparticles (NPs) on Si substrates. The NPs are bound into the film by p-toluenesulfonic acid (PTSA) and the film is made to absorb volatile organic compounds (VOCs). Since the color of the sensing element depends on the interference of reflected light from the surface of the film and from the film/silicon substrate interface, colorimetric detection is possible by the varying thickness of the NP-based film. Indeed, VOC absorption causes significant swelling of the film. Thus, the optical path length is increased, interference wavelengths are shifted and the refractive index of the film is decreased. This causes a change of color of the sensor element visible by the naked eye. The color response is rapid and changes reversibly within seconds of exposure. The sensing element is extremely simple and cheap, and can be fabricated by common coating processes.
Keywords: colorimetric gas sensing; p-toluenesulfonic acid (PTSA); TiO2 nanoparticles

(untitled) - Burgess, I. B.; Lončar, M.; Aizenberg, J. (J. Mater. Chem. C, 2013)

(untitled) - Hong, W.; Li, H.; Hu, X.; Zhao, B.; Zhang, F.; Zhang, D. (Chem. Commun., 2012)

(untitled) - Singleton, T. A.; Burgess, I. B.; Nerger, B. A.; Goulet-Hanssens, A.; Koay, N.; Barrett, C. J.; Aizenberg, J. (Soft Matter, 2014)

(untitled) - Hong, W.; Chen, Y.; Feng, X.; Yan, Y.; Hu, X.; Zhao, B.; Zhang, F.; Zhang, D.; Xu, Z.; Lai, Y. (Chem. Commun., 2013)

(untitled) - Diao, Y. Y.; Liu, X. Y.; Toh, G. W.; Shi, L.; Zi, J. (Adv. Funct. Mater., 2013)

(untitled) - Zhang, Y.; Qiu, J.; Gao, M.; Li, P.; Gao, L.; Heng, L.; Tang, B. Z.; Jiang, L. (J. Mater. Chem. C, 2014)

(untitled) - Lu, G.; Farha, O. K.; Kreno, L. E.; Schoeneker, P. M.; Walton, K. S.; van Duyne, R. P.; Hupp, J. T. (Adv. Mater., 2011)

(untitled) - Scolan, E.; Sanchez, C. (Chem. Mater., 1998)

(untitled) - Joost, U.; Saarva, A.; Visnapuu, M.; Nõmmiste, E.; Utt, K.; Saar, R.; Kisand, V. (Ceram. Int., 2014)

(untitled) - Joost, U.; Juganson, K.; Visnapuu, M.; Mortimer, M.; Kahru, A.; Nõmmiste, E.; Joost, U.; Kisand, V.; Ivask, A. (J. Photochem. Photobiol., B: Biol., 2015)

Spectroscopic Ellipsometry Principles and Applications - Fujiwara, H. (John Wiley & Sons Ltd., 2007)

(untitled) - Seah, M. P.; Gilmore, I. S.; Spencer, S. J. (J. Electron Spectrosc. Relat. Phenom., 2001)

CasaXPS, version 2.3.12 (Casa Software Ltd., 2000)

(untitled) - Enkovaara, J.; Rostgaard, C.; Mortensen, J. J.; Chen, J.; Dułak, M.; Ferrighi, L.; Gavnholt, J.; Glinsvad, C.; Haikola, V.; Hansen, H. A.; Kristoffersen, H. H.; Kuisma, M.; et al. (J. Phys.: Condens. Matter, 2010)

(untitled) - Mortensen, J. J.; Hansen, L. B.; Jacobsen, K. W. (Phys. Rev. B, 2005)

(untitled) - Blöchl, P. E. (Phys. Rev. B, 1994)

(untitled) - Bonifacio, L. D.; Puzzo, D. P.; Breslav, S.; Willey, B. M.; McGeer, A.; Ozin, G. A. (Adv. Mater., 2010)

(untitled) - Bonifacio, L. D.; Ozin, G. A.; Arsenault, A. C. (Small, 2011)

(untitled) - Li Bassi, A.; Cattaneo, D.; Russo, V.; Bottani, C. E.; Barborini, E.; Mazza, T.; Piseri, P.; Milani, P.; Ernst, F. O.; Wegner, K.; Pratsinis, S. E. (J. Appl. Phys., 2005)

(untitled) - Hashimoto, S.; Tanaka, A. (Surf. Interface Anal., 2002)

(untitled) - Dhayal, M.; Sharma, S. D.; Kant, C.; Saini, K. K.; Jain, S. C. (Surf. Sci., 2008)

Gaussian 09, Revision A. 02 (Gaussian Inc., 2009)

(untitled) - Perdew, J. P.; Burke, K.; Ernzerhof, M. (Phys. Rev. Lett., 1996)

(untitled) - Ernzerhof, M.; Perdew, J. P. (J. Chem. Phys., 1998)

Quantum Chemistry - McQuarrie, D. A. (University Science Books, 2008)

(untitled) - Scuseria, G. E. (J. Phys. Chem. A, 1999)

(untitled) - Fantin, P. A.; Barbieri, P. L.; Neto, A. C.; Jorge, F. E. (J. Mol. Struct.: THEOCHEM, 2007)

(untitled) - Weigend, F.; Ahlrichs, R. (Phys. Chem. Chem. Phys., 2005)

(untitled) - Ljungberg, M. P.; Mortensen, J. J.; Pettersson, L. G. M. (J. Electron Spectrosc. Relat. Phenom., 2011)

(untitled) - Nasef, M. M.; Saidi, H. (Appl. Surf. Sci., 2006)